Universal Approach to Rapid Amplified Plasmonic Sensing Using Helix Defect Phase Transition Polymers. (2nd February 2021) - Shugayev, Roman; Devkota, Jagannath; Kim, Ki‐Joong; Cvetic, Patricia; Ohodnicki, Paul
Abstract: Permittivity sensing is a critically important analytical tool for bioscience, environmental, and industrial applications. The response time for commonly used plasmonic permittivity sensors is fundamentally set by the reaction kinetics of chemically adsorbed analytes. In this work, the proposal is to overcome this limit by combining plasmonic sensors with phase transition materials possessing a rapid amplified electrostatic response such as quadrupole moment induced molecular helix reversal. As a proof‐of‐concept, rapid sensing of CO2 on a phase transition polytetrafluoroethylene substrate and amplification of permittivity response in plasmonic Fabry–Perot sensor is shown. The demonstrated universal approach holds promise for a wide range of applications in fast, real time sensing and monitoring of biological and environmental processes. Abstract : Plasmonic permittivity sensing provides a wide array of data for breakthrough biomedical research and environmental applications. In this work, a new universal mechanism of quadrupole moment‐induced molecular helix reversal is demonstrated. This mechanism greatly enhances the permittivity change of the plasmonic sensor and exhibits a near‐instantaneous rapid response to the addition of gas molecules.